Evaluation of the use of vinasse as a biostimulation agent for the biodegradation of oily sludge in soil - Crivelaro, Sérgio Henrique Rezende [UNESP]; Mariano, Adriano Pinto [UNESP]; Furlan, Luis Tadeu; Gonçalves, Renato Almeida; Seabra, Paulo Negrais; de Angelis, Dejanira de Franceschi [UNESP] (FapUNIFESP (SciELO), 2010)
This work aimed to study the effect of vinasse on the biodegradation in soil of oily sludge from the Replan-Petrobras oil refinery. The Bartha respirometric method was used to verify the efficiency of the treatments with soil, oily sludge (7 and 14% m/m) and soil moisture adjustment with or without vinasse (0.11 mL/g dry soil) for 121 days. Although an increase in the soil microbial population was obtained with the vinasse, it demonstrated not to be adequate to enhance the biodegradation efficiency of the oily sludge in soil, since there was no difference between the CO2 produced from treatments with or without vinasse after the complete consumption of the vinasse. Thus, the use of vinasse as an amendment to biodegradation processes showed not to be efficient under the studied conditions.
Keywords: Biodegradation; Landfarming; Oily sludge; Soil; Vinasse